PRMT5-Mediated Arginine Methylation of ACSL4 Attenuates Its Stability and Suppresses Ferroptosis in Renal Cancer - Meng Zhang; Hao Liu; Rong Yin; Jiayu Xu; Siqi Fan; Xingyou Qian; Menghan Cao; Shu Li; Ao Zhang; Guodong Chen; Hongmei Yong; Zhongwei Li; et al. (Research)
Lipid-peroxidation-driven ferroptosis represents a vital mode of regulated cell death increasingly recognized for its role in cancer therapy. Lipid metabolism plays a crucial role in determining the vulnerability of cells to ferroptosis, particularly in cancer cells. The biosynthesis and remodeling of polyunsaturated fatty acid–phosphatidylethanolamine in cell membranes rely heavily on the activity of acyl-CoA synthetase family member 4 (ACSL4). However, the regulatory mechanisms governing ACSL4 expression in renal cell carcinoma (RCC) remain unclear. In this study, we screened a library of 765 epigenetic compounds to identify novel regulators of ferroptosis. Notably, we discovered that protein arginine methyltransferase 5 (PRMT5) inhibitors markedly promote ferroptosis in RCC cells. Inhibition or knockdown of PRMT5 in RCC cell lines enhanced lipid peroxidation and reduced cell viability. PRMT5 interacted with and catalyzed the symmetric dimethylation of ACSL4 at the arginine 549 (R549) site, facilitating its degradation via the proteasome. In vivo, the combination of a PRMT5 inhibitor with anti-PD-1 therapy notably increased ferroptosis and reduced tumor growth. Furthermore, elevated PRMT5 levels were associated with unfavorable clinical outcomes in patients with renal cancer. Overall, our findings suggest that PRMT5 regulates ferroptosis in RCC by methylating ACSL4 at the R549 site, and its inhibition enhances the therapeutic efficacy of immunotherapy through the induction of ferroptosis.